Analysis of Isocitrate dehydrogenase (IDH) mutation in Gliomas—a call for neurosurgeons and pathologists in Pakistan - Masood, Muntaha; Rana Fayyaz Anwar; Khalid Mehmood; Maham Javed; Tuaha Amjad; Nadia Naseem (Journal of the Pakistan Medical Association, 2022)
Tumours of the central nervous system, though not very common, pose a serious health burden owing to their high mortality rate. Glial tumours are the commonest type of brain tumours in Pakistani population. Diagnosis of gliomas has been greatly revolutionised over the past few years with integration of immunohistochemistry and molecular subtyping in the World Health Organisation’s updated 2016 classification of glial tumours. One of the major changes was incorporation of isocitrate dehydrogenase mutation detection that is considerably a significant prognostic and predictive marker. The published data on isocitrate dehydrogenase mutation in the local population is hard to find. The current narrative review was planned to briefly describe the international trends regarding frequency of isocitrate dehydrogenase mutation in gliomas, its predictive and prognostic significance and its impact on accurate diagnosis leading to a targeted therapeutic approach for patients. Key Words: Gliomas, Isocitrate dehydrogenase 1, Mutation, Classification, Prognosis, Treatment.